Macromammalian faunas, biochronology and palaeoecology of the early Pleistocene Main Quarry hominin-bearing deposits of the Drimolen Palaeocave System, South Africa - Adams, Justin W. (PeerJ, 2016)
The Drimolen Palaeocave System Main Quarry deposits (DMQ) are some of the most prolific hominin and primate-bearing deposits in the Fossil Hominids of South Africa UNESCO World Heritage Site. Discovered in the 1990s, excavations into the DMQ have yielded a demographically diverse sample of Paranthropus robustus (including DNH 7, the most complete cranium of the species recovered to date), early Homo, Papio hamadryas robinsoni and Cercopithecoides williamsi. Alongside the hominin and primate sample is a diverse macromammalian assemblage, but prior publications have only provided a provisional species list and an analysis of the carnivores recovered prior to 2008. Here we present the first description and analysis of the non-primate macromammalian faunas from the DMQ, including all 826 taxonomically identifiable specimens catalogued from over two decades of excavation. We also provide a biochronological interpretation of the DMQ deposits and an initial discussion of local palaeoecology based on taxon representation.The current DMQ assemblage consists of the remains of minimally 147 individuals from 9 Orders and 14 Families of mammals. The carnivore assemblage described here is even more diverse than established in prior publications, including the identification of Megantereon whitei, Lycyaenops silberbergi, and first evidence for the occurrence of Dinofelis cf. barlowi and Dinofelis aff. piveteaui within a single South African site deposit. The cetartiodactyl assemblage is dominated by bovids, with the specimen composition unique in the high recovery of horn cores and dominance of Antidorcas recki remains. Other cetartiodactyl and perissodactyl taxa are represented by few specimens, as are Hystrix and Procavia; the latter somewhat surprisingly so given their common occurrence at penecontemporaneous deposits in the region. Equally unusual (particularly given the size of the sample) is the identification of single specimens of giraffoid, elephantid and aardvark (Orycteropus cf. afer) that are rarely recovered from regional site deposits. Despite the diversity within the DMQ macromammalian faunas, there are few habitat- or biochronologically-sensitive species that provide specific ecologic or age boundaries for the deposits. Recovered species can only support the non-specific, mixed open-to-closed palaeohabitats around Drimolen that have been reconstructed for the other penecontemporaneous South African palaeokarst deposits. The identified Equus quagga ssp. specimens recovered from the floor of the current excavation (∾−4.5–5 m below datum) suggests that most, if not all the DMQ specimens, were deposited after 2.33 Ma. Simultaneously, the carnivore specimens (D. cf. barlowi, L. silberbergi) suggest earlier Pleistocene (pre- 2.0–1.8 Ma) to maximally 1.6 Ma deposition (D. aff. piveteaui) for most of the DMQ fossil assemblage.